PENILAIAN KEMUNCAK DAN ARCA MENURUT BALAI PELESTARIAN CAGAR BUDAYA JAWA TIMUR - Khildun Nimah, Kubiyah; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2019)
This research aims to identify the assessment of peak and statue according to the East Java Cultural Heritage Conservation Centre. This research uses descriptive-qualitative method. The result of this research is that the peak using estimation from many experts, but they use fair value, replacement value, comparative value, and important value as the basic to estimate the value. Statue of Agastya is summing fair value and replacement value. After that, important value was counted by using Delphi scale, in which 0 is considered not important, 1 is quite important, 2 is important, 3 is very important. Then, it?s converted in the form of percentage: 0% is considered not important, 25% is quite important, 50% is important, and 75%-100% is very important. The percentage of the important value is multiplied by replacement value. Then, the results are summed with the replacement value.Keywords: Historical Assets, Assessment of historic assets, peak, statues